Screening for asymptomatic neurosyphilis in HIV patients after treatment of early syphilis: an observational study. (14th February 2017) - Tomkins, Andrew; Ahmad, Shazaad; Cousins, Darren E; Thng, Caroline M; Vilar, Francisco Javier; Higgins, Stephen P
Abstract : Objective: To determine the prevalence of asymptomatic neurosyphilis (ANS) in HIV-positive individuals after treatment of early syphilis with single-dose benzathine penicillin G (BPG) or oral antibiotic alternatives. Methods: Patients at high risk of neurosyphilis (defined by serum rapid plasma reagin (RPR) titre ≥1:32 and/or peripheral blood CD4 lymphocyte count ≤350/μL) underwent lumbar puncture (LP) at a median time of 8.2 months post treatment. ANS was diagnosed by a reactive cerebrospinal fluid (CSF) RPR test or CSF white blood cells (WBC) >20/μL plus a reactive CSF Treponema pallidum particle agglutination (TPPA) ≥1:640. Results: Of 133 eligible patients, all were men who have sex with men. Of these, 64 consented to LP. Full CSF results were available for 59 patients. Inclusion criteria were serum RPR (21/59), CD4 count (22/59) and combined RPR and CD4 (16/59). The LP patients were white British (82%), median age 40. Syphilis stages were primary (17%) secondary (43%) and early latent (41%). Syphilis was treated with BPG (47/59), doxycycline 100 mg two times per day for 14 days (10/59) and for 21 days (1/59). Azithromycin 500 mg one time per day for 10 days was given to 1/59. At the time of LP, 100% of patients had achieved serological cure, and 66% were taking antiretroviral treatment. Only 1/59 was diagnosed with ANS. The CSF showed: RPR non-reactive (59/59); TPPA non-reactive in 54/59; WBC ≤5/μL in 51/59. Conclusions: Although the number of patients in our study is modest, single-dose BPG appears to be highly effective even in patients at high risk of neurosyphilis.